Jurnal Akuntansi, Manajemen Dan Ekonomi 2022
DOI: 10.32424/1.jame.2022.24.2.5410
|View full text |Cite
|
Sign up to set email alerts
|

Gen Z’s Gender, Hedonic Shopping Motives and Impulse Buying

Abstract: The usage of cheap internet access via cell phones, along with the fact that Gen Z is growing up in the era of globalization, has resulted in a generation that is completely reliant on the internet. The goal of this study was to see how hedonic shopping motives and gender influenced Gen Z's impulse internet purchases. The participants in this study were Management Study Program students who made online purchases through Shopee. The participants in this study are management students between the ages of 18 and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Hedonic motivation is feelings of pleasure, excitement, or satisfaction stimulated by applying technology. Venkatesh et al (2012) in Rosmaniar (2022) found that elements such as happiness, joy, and enjoyment reflect hedonic motivation and act as essential factors in customer acceptance of technology (Viswanath Venkatesh, 2012).…”
Section: Hedonic Motivationmentioning
confidence: 99%
“…Hedonic motivation is feelings of pleasure, excitement, or satisfaction stimulated by applying technology. Venkatesh et al (2012) in Rosmaniar (2022) found that elements such as happiness, joy, and enjoyment reflect hedonic motivation and act as essential factors in customer acceptance of technology (Viswanath Venkatesh, 2012).…”
Section: Hedonic Motivationmentioning
confidence: 99%